2022
DOI: 10.1109/access.2022.3213644
|View full text |Cite
|
Sign up to set email alerts
|

Offensive Security: Cyber Threat Intelligence Enrichment With Counterintelligence and Counterattack

Abstract: Cyber-attacks on financial institutions and corporations are on the rise, particularly during pandemics. These attacks are becoming more sophisticated. Reports of hacking activities against government and commercial sector organisations have garnered a lot of attention in the last several years. By design, the focus of Cyber Threat Intelligence (CTI) is exclusively defensive. This is because most of the CTI-derived analysis output is intended to prevent breaches or facilitate early detection. So, there is a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…CTI focuses primarily on defense against these attacks, but there is a need for new methods to unmask attackers. Rana et al [ 38 ] created malicious files as decoys, allowing the authors to gather information from susceptible PCs using honeypots. They used various tools for data analysis, including Visual Studio Code and Python.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CTI focuses primarily on defense against these attacks, but there is a need for new methods to unmask attackers. Rana et al [ 38 ] created malicious files as decoys, allowing the authors to gather information from susceptible PCs using honeypots. They used various tools for data analysis, including Visual Studio Code and Python.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation method uses counterintelligence techniques such as cyber deception and decoy files to obtain adversary information. Overall, this research focuses on providing better proactive adversarial system intelligence by capturing attackers’ system information through accurate document-based tokens in a proactive defensive environment while executing threat hunting with TTPs (Tactics Techniques Procedures) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Port-based classification or flow-based analysis and Deep Packet Inspection (DPI) are frequently used in these techniques [28]. These techniques have, however, a number of drawbacks, such as the requirement for thorough payload inspection, vulnerability to evasion strategies, and reliance on wellknown port numbers [2].…”
Section: Traditional Vpn Classification Methodsmentioning
confidence: 99%
“…These countries have enforced laws making VPN use on phones illegal, accompanied by severe fines and potential imprisonment. Such measures underscore the increasing focus on VPN usage globally, particularly when they are employed to circumvent geo-restrictions and access blocked content, raising significant issues regarding cybersecurity and national security [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Riesco et al [8] suggested using smart contracts and blockchain technology to encourage information sharing and create dynamic risk-management systems that may instantly reduce cyber risks. Using Python and Visual Studio Code for data analysis, Rana et al [9] used malicious files as decoys to extract information from susceptible systems.…”
Section: Introductionmentioning
confidence: 99%